ANALYTICAL FOUNDATIONS OF ELECTROTECHNOLOGICAL TREATMENT METHODS FOR AGRICULTURAL CROP SEEDS - Makhmudov Nuriddin Makhamadali o‘g‘li; Mukhtorjonov Shohruh Muzaffar o‘g‘li (Web of Journals Publishing, 2025)
The article presents an analysis of devices that enhance the efficiency of electrotechnological treatment of agricultural crop seeds.
Keywords: Seed, laboratory, field, physico-mechanical, electric field, biological, opposite, field, dispersibility, density, electric sorter device, ultraviolet light, equipment, pneumatic, mechanical, seedling.